Analysis of Participation of Active Fishers in the Production of Inland Fisheries and Aquaculture in Sri Lanka - Baweithra, U. (University of Jaffna, 2016)
Inland Fisheries and Aquaculture (IFA) contribute about 25% to the world's production of fish. Development of IFA in Sri Lanka has been given high priority by the Government. Sri Lanka plans to double inland fisheries production by supporting aquaculture to make up for dwindling ocean fish stocks.It will ensure production of fish as a cheap source of animal protein for the rural communities and it has the potential to increase income and employment opportunities for the low income people. So, it provides livelihood to the rural communities in the interior districts. The main aim of this study is to investigate the participation of the active fishers (engaged in IFA among fishing households) in the production of IFA based on their province. The data was obtained from the Performance Report 2015 of National Aquaculture Development Authority of Sri Lanka (NAQDA) and Sri Lankan Labour Force Survey 2015 of Department of Census and Statistics. The relationship between the variables was investigated by estimating odds ratios at corresponding 95% confidence interval. The results revealed that the labour force on agricultural industry among the economically active population was comparatively higher in Uva and North Central Provinces than the other seven provinces. The participation of active female fishers and active male fishers in IFA was comparatively higher in Northern Province and North Western Province than the other provinces respectively. Based on the comparison of active fishers and the annual production of IFA, North Western and North Central Provinces shown positive production gain and Central and Western Provinces shown negative production gain in the year of 2015 respectively. From this analysis, we concluded that the active fishers especially male fishers from the province of North Western were highly contributed to the annual production of IFAin the year of 2015.
Keywords: Inland fisheries-aquaculture; Odds-ratio; Provinces